Investigation of the association between cardio-metabolic risk factors, neurotrophins and gastric hormones among apparently healthy women: A cross-sectional analysis - Reihaneh Zeinalian; Dorsa Arman Moghadam; Naseh Pahlavani; Neda Roshanravan; Mohammad Alizadeh; Masoumeh Jabbari; Sorayya Kheirouri (Journal of Cardiovascular and Thoracic Research, 2022)
Introduction: Although, some evidence has shown that obestatin, ghrelin, and neurotrophic factors can be involved in the development of cardio-metabolic risk factors, there are some contradictions in this regard. We aimed to investigate the association of serum neurotrophic factors and some gastric hormones with cardio-metabolic risk factors among apparently healthy women. Methods: In the present study, 90 apparently healthy women were recruited by a convenient sampling method from the nutrition counseling clinic in Tabriz, Iran. All participants need dietary counseling for weight loss and were recruited before receiving any dietary interventions. Anthropometric, biochemical, physical activity, and blood pressure (BP) measurements, as well as dietary assessment, were done in all participants. Results: Women who were in the highest tertile of serum obestatin levels (OR=0.118, 95% CI:0.035-0.396) had a significantly lower risk for development of hypertriglyceridemia compared to the reference group (P trend<0.001). Participants in the highest tertile of serum ghrelin had a significant lower risk of hypertriglyceridemia, hyperglycemia, low HDL-C, and MetS (Ptrend<0.05). Women who were in the higher tertile of serum NGF levels had a significantly lower risk for development of hypertriglyceridemia after adjustment for potential confounding variables (OR=0.091, 95% CI: 0.023-0.361 and OR=0.193, 95% CI: 0.057-0.649 respectively). Conclusion: In the current study serum levels of obestatin, NGF, and ghrelin were associated with some cardio-metabolic risk factors such as hypertriglyceridemia and MetS. It seems that these factors are associated with metabolic regulation. However, further studies are needed to substantiate this claim.